Novel benzodithiophene-TTBTBTT copolymers: synthesis and investigation in organic and perovskite solar cells. Issue 15 (28th June 2022) - Komissarova, Ekaterina A.; Kuklin, Sergei A.; Maskaev, Andrey V.; Latypova, Alina F.; Kuznetsov, Petr M.; Emelianov, Nikita A.; Nikitenko, Sergei L.; Martynov, Ilya V.; Kuznetsov, Ilya E.; Akkuratov, Alexander V.; Frolova, Lyubov A.; Troshin, Pavel A.
Abstract : New conjugated (BDT-TTBTBTT) n copolymers are featured as promising hole-transport materials for n–i–p perovskite solar cells delivering efficiencies of up to ∼19%. Abstract : A series of new conjugated polymers has been synthesized and investigated as absorber and hole-transport layer materials, respectively, in organic and perovskite solar cells (OSCs and PSCs). Organic solar cells were assembled using fullerene ([C60]PCBM) and in some cases also non-fullerene acceptors such as ITIC-M, EH-IDTBR and O-IDTBR. A strong impact of the chemical structure of the synthesized polymers on the performance of organic solar cells has been revealed. The introduction of fluorine atoms in the thiophene rings and, in particular, using fluorinated phenyl substituents in the benzodithiophene fragment resulted in improved open-circuit voltages as compared to those of structurally similar polymers comprising neither fluorine atoms nor phenyl residues. Furthermore, the performance characteristics of OSCs were correlated with the nanoscale morphology of the composite films revealed by atomic force microscopy and infrared scattering near-field optical microscopy (IR s-SNOM) techniques. The polymer film uniformity also impacted the performance of perovskite solar cells, and so the highest efficiency of 18.8% was obtained using a conjugated polymer with the best film formation properties induced by branched solubilizing side chains. Thus, the obtained results improve the understanding of the relationship between the polymer structure and the device photovoltaic performance, which is of crucial importance for the rational design of new polymeric materials for efficient and stable OSCs and PSCs.